Prevalence of Malocclusion in Eastern Nepal - Shrestha, Suja; Giri, Abhishek; Kafle, Dashrath; Shrestha, Sakun; Bhattarai, Maria; Poudel, Pratibha; Mahanta, Swagat Kumar (Journal of College of Medical Sciences-Nepal, 2024)
Background Malocclusion is the abnormal relationship between upper jaw and lower jaw. It is third most common prevalent oral pathology. Different environment may contribute to malocclusion, so treatment may also vary likewise. Determining the prevalence of malocclusion of different geographic region, ethnic groups and gender helps to identify the distribution of malocclusion, which in turn aids in preventive treatments. This study is an attempt to assess the prevalence of malocclusion among the individuals of eastern Nepal. Methods Data collection was done by direct observation of the patients using probe and mouth mirror. Descriptive cross-sectional study method was used in this research. The malocclusion based on Angle’s classification, overjet, overbite, open bite, crowding, spacing and cross bites were recorded. Results A total of 429 patients were included in the study. Among them, 190 (44.3%) were males and 239 (55.7%) were females with male: female ratio 1:1.3. The mean age of patients was found to be 26.92 ±10.61years with the age range of 12- 65 years. Angle’s class I (75.1%) was the most prevalent malocclusion whereas Angle’s class III was observed in 16.6% of total samples followed by Angle’s class II (8.4%). Conclusions The most prevalent malocclusion in our study is Angle’s class I in both male and female patients. Crowding was the most prevalent occlusal traits observed whereas open bite was the least.